Déclarations de risque et bénéficiaires d’assurance-vie : de certaines énigmes léguées par le rédacteur du nouveau Code - Lluelles, Didier (Assurances, 1995)
Professor Didier Lluelles examines two enigmatic insurance provisions introduced in the new Quebec Civil Code: the disappearance of the term "reasonable insurer" contained in the previous Code, but which does not appear in the new one and the ambiguity of the new article 2466, paragraph 1, on any change in the policy period "that increases the risks stipulated in the policy and that results from events within his (the insured's) control". He also discusses innovations regarding the designation of a beneficiary (article 2447 paragraph 2) and the non-application of the rules respecting representation with respect to insurance matters (article 2456).